PATHOMORPHOLOGICAL CHANGES IN THE LIVER IN UREMIA (World Bulletin of Public Health, 2025)
Uremia, a clinical syndrome caused by the accumulation of nitrogenous waste products due to renal insufficiency, has systemic consequences, affecting multiple organs, including the liver. Although primarily a consequence of kidney failure, uremia can significantly alter liver morphology and function, despite the liver not being a direct target of uremic toxins. This article explores the pathomorphological changes observed in hepatic tissue during uremic conditions, including cellular degeneration, vascular alterations, fibrosis, and immunopathological responses.
Keywords: uremia; pathomorphology; liver; fibrosis